FLUID INCLUSION STUDIES OF THE EPITHERMAL QUARTZ VEINS FROM SUALAN PROSPECT, WEST JAVA, INDONESIA - Myo Min Tun; I Wayan Warmada; Arifudin Idrus; Agung Harijoko; Okki Verdiansyah; Koichiro Watanabe (Geological Engineering Department Universitas Gadjah Mada, 2015)
Sualan prospect is located at Talegong Sub-district of Garut Regency, West Java, Indonesia. The area constitutes calc-alkaline volcanic and volcaniclastic rocks of Tertiary age. The rocks have experienced regional propylitic and argillic alteration. Fluid inclusions from quartz veins were studied in order to constrain the nature, characteristics and evolution of fluids. Microthermometric measurements on fluid inclusion were carried out by freezing and heating experiment. Temperatures of homogenization (Th) and final melting of ice (Tm) were measured for primary, liquid-dominated, two-phase inclusions. The values of Th range from 160°C to 210°C and salinities range from 0.35 to 4.96 wt.% NaCl equiv. Formation temperature of the quartz veins are estimated at 180°C and 190°C and paleo-depth of formation are at 80m and 140m, respectively. Microthermometric data indicates that fluid mixing and dilution were important processes during the evolution of hydrothermal system. Based on fluid inclusion types, microthermometric data, trapping temperature, paleo-depth, texture of quartz and hydrothermal alteration types, quartz veins from prospect were developed under epithermal environment. Keywords: Quartz vein, fluid inclusions, microthermometry, salinities, formation temperature, paleo-depth, epithermal, Sualan prospect.